2010
DOI: 10.1124/dmd.110.033886
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Induction of Cytochrome P450 Enzyme Activity by Statins Using a New Liquid Chromatography-Tandem Mass Spectrometry Cocktail Assay in Human Hepatocytes

Abstract: ABSTRACT:Human hepatocytes in primary culture are a very useful model to directly assess induction of gene expression by xenobiotics. We developed a cytochrome P450 (P450) activity cocktail assay using model substrates for the seven important P450s 1A2 (phenacetin), 2B6 (bupropion), 2C8 (amodiaquine), 2C9 (tolbutamide), 2C19 (Smephenytoin), 2D6 (propafenone), and 3A4 (atorvastatin). Metabolite formation was determined by liquid chromatography-tandem mass spectrometry in hepatocyte culture supernatants. Atorvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…This was mainly due to the enormous variability between PHH donors. We observed a decline in basal P450 activities during the first day of culture period, which was previously reported in primary hepatocytes (Feidt et al, 2010;Lübberstedt et al, 2011). In the HepaRG cells, much better preservation of the six measured P450 activities over the investigated culture period of 72 hours was observed, in agreement with previous studies (Kanebratt and Andersson, 2008;Turpeinen et al, 2009;Lübberstedt et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was mainly due to the enormous variability between PHH donors. We observed a decline in basal P450 activities during the first day of culture period, which was previously reported in primary hepatocytes (Feidt et al, 2010;Lübberstedt et al, 2011). In the HepaRG cells, much better preservation of the six measured P450 activities over the investigated culture period of 72 hours was observed, in agreement with previous studies (Kanebratt and Andersson, 2008;Turpeinen et al, 2009;Lübberstedt et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Measurement of P450 Enzyme Activities. Cytochrome P450 enzyme activities were determined in PHH and HepaRG cell culture supernatants using a liquid chromatography with tandem mass spectrometry-based substrate cocktail assay, as described previously (Feidt et al, 2010). CYP2D6 enzyme activity (propafenone 5-hydroxylation) was not quantifiable in HepaRG cells by liquid chromatography-tandem mass spectrometry cocktail assay and was therefore excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We are not aware of any clinical studies demonstrating that bupropion inhibits CYP1A2 activity. In human liver microsomes in vitro, bupropion incubated with melatonin or phenacetin (probes for CYP1A2) shows no inhibitory effects on CYP1A2-mediated pathways [14][15][16]. Chlorzoxazone and caffeine have been dosed together in several metabolic cocktail approaches to phenotype CYP enzymes without any detected metabolic interactions [17][18][19].Thus, there is no known interaction between the study medications affecting the phenotyping of CYP1A2.…”
mentioning
confidence: 99%
“…A recent study that profiled the induction of the CYP450 activity in human hepatocytes by statins using a new liquid chromatography technique, a tandem mass spectrometry cocktail assay, showed that all statins, except pravastatin, induce the P450 activity to some degree, approximately in the order of atorvastatin > simvastatin > lovastatin > rosuvastatin. The inducibility of P450s occurred in the order of CYP2C8 > CYP3A4 > CYP2C9 > CYP2B6 > CYP2C19 ≈ CYP2D6 > CYP1A2 27) . The higher potential of atorvastatin to induce the CYP450 system may play a role in potentiating the conversion of clopidogrel to its active metabolite and hence its antiplatelet effects.…”
Section: Study Limitationsmentioning
confidence: 99%